Anatomy of an international norm entrepreneur: The friends of fossil fuel subsidy reform - Rive, V (Cambridge University Press, 2018)
This comprehensive volume provides the first book-length account on the politics of fossil fuel subsidies. This title is also available as Open Access.
Keywords: Business & Economics; Law; International; Fossil fuel subsidies; International relations; Climate change